FEATURES OF PROFESSIONAL INTERACTIONS OF FUTURE SPECIALISTS OF SOCIONOMIC PROFESSIONS IN THE INCLUSIVE ENVIRONMENT: SWOT-ANALYSIS - Nakhod, Svitlana (Educological discourse, 2020)
The article is devoted to the SWOT-analysis of the features of professional interaction of future specialists of socionomic professions in an inclusive environment. The socio-pedagogical and psychological direction of the following socionomic professions is considered: psychologist, pedagogue, social pedagogue, social worker, tutor. The strengths of professional interaction of specialists are clarified: the ability to jointly set goals and distribute the functions of professional activity, identify ways to achieve them and plan this process; to establish sequence in the working process; analyze the results of diagnosis of individual characteristics of the child; use theoretical knowledge to solve practical problems of professional activity, etc. Weaknesses include translation of information in professional terminology; implementation of holistic reflection; division of responsibilities; specification of achieving meta-subject results. Opportunities are found in improving the efficiency of working with a particular child; holistic view of the child; ability to individualize the educational process taking into account the results of diagnostics, designing an adaptive learning strategy; providing effective assistance to the child in overcoming communicative, regulatory, cognitive and personal difficulties in the educational process, etc. Threats to the establishment of effective professional interaction were manifested in communicative unpreparedness of the parties, unwillingness to work in a team, insufficient understanding by specialists of their own functions in the field of psychological and pedagogical support of a child with special educational needs. It is concluded that joint, specially organized educational activities of future specialists of socionomic professions will contribute to a strong and meaningful acquisition of theoretical knowledge, acquisition of practical skills and experience of professional communication. It is established that the implementation of the program of joint training of teachers, psychologists, tutors, social educators, social workers will help create a single field that will unite future professionals in the process of forming integrative competencies needed to work in inclusive education.